Mapping between two models of etching process - Patsahan, T.; Taleb, A.; Stafiej, J.; Badiali, J.-P. (Condensed Matter Physics, 2007)
We consider two models for the etching processes using numerical simulations based on cellular-automata
discrete-lattice approach. In one model we use a uniform etching probability for each surface site. In another
model the etching probability at a given site depends on the local environment of this site. In contrast to the
first model we have now a non-local description of the surface evolution. It is natural to consider the following
question: is this non-locality sufficient to induce new physics? To answer this question is the main goal of
the paper. We show that there exists an equivalence between the two models. This means that the non-local
model gives results similar to the local one provided we use an effective value of the etching probability. Використовуючи комп’ютерне моделювання на основi комiркового автомату, дослiджено двi гратковi моделi, якi описують процеси витравлювання. В однiй моделi використано однакову iмовiрнiсть витравлювання для всiх поверхневих вузлiв. В iншiй моделi iмовiрнiсть витравлювання вузла залежить вiд оточення даного вузла. Таким чином, на противагу першiй моделi, в другiй моделi присутнiй нелокальний опис розвитку поверхнi. Тому природно розглянути наступне питання: чи ця нелокальнiсть є достатньою, щоб спричинити якiсно новi результати? Вiдповiдь на дане запитання є основною метою цiєї роботи. Показано, що iснує еквiвалентнiсть мiж двома розглянутими моделями. Це значить, що нелокальна модель приводить до якiсно подiбних результатiв, що i локальна модель, яка описується певною ефективною iмовiрнiстю витравлювання.